Who is attracted and why? How agile project management influences employee's attraction and commitment. Issue 3 (23rd August 2020) - Koch, Jan; Schermuly, Carsten C.
Abstract : Purpose: In times of market volatility and uncertainty, finding effective strategies to attract and retain individuals continues to be a challenge for organizations. Based on the psychological empowerment process (Spreitzer, 1996), this paper strives to examine if the application of agile project management could serve as such a strategy. Design/methodology/approach: In two independent studies, the authors used an experiment with students as potential applicants ( N  = 121) and a field study with employees ( N  = 229) to test the predictive quality of agile project management for attracting individuals toward the organization. Findings: Using structural equation modeling, the authors identified an indirect relationship between agile project management and attraction toward the organization via psychological empowerment. The authors found this relationship for potential applicants as well as employees. Furthermore, individuals high in sensation seeking are found to be more attracted toward organizations that apply agile project management than individuals low in sensation seeking. Research limitations/implications: The findings contribute to the empowerment literature by establishing agile project management as a work structure that fosters feelings of psychological empowerment. Practical implications: Taken together, these results suggest that agile project management can attract individuals who seek novel, complex and intense sensations. Where applicable, organizations may highlight their practice of agile project management methodologies as part of their employer brand to attract future specialists for agile projects. Originality/value: This paper is the first to integrate the research streams on agile project management and attraction toward the organization using quantitative data.